2013
DOI: 10.1002/cphc.201300516
|View full text |Cite
|
Sign up to set email alerts
|

Selective Adsorption of Functionalized Nanoparticles to Patterned Polymer Brush Surfaces and Its Probing with an Optical Trap

Abstract: The site-specific attachment of nanoparticles is of interest for biomaterials or biosensor applications. Polymer brushes can be used to regulate this adsorption, so the conditions for selective adsorption of phosphonate-functionalized nanoparticles onto micropatterned polymer brushes with different functional groups are optimized. By choosing the strong polyelectrolytes poly(3-sulfopropyl methacrylate), poly(sulfobetaine methacrylate), and poly[2-(methacryloyloxy)ethyl trimethylammonium chloride], it is possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…We model the solvent as a Lennard-Jones (LJ) liquid and the polymer as linear chains of 100 beads connected by permanent bonds. All solvent and polymer beads have a mass m and interact through a standard LJ 12-6 pairwise potential, U LJ (r) = 4ǫ[(σ/r) 12 − (σ/r) 6 − (σ/r c ) 12 + (σ/r c ) 6 ], where r is the distance between the centers of two beads, ǫ the strength of interaction, and σ the size of beads. The cut off distance is r c = 3.0σ for all nonbonded pairs and r c = 2 1/6 σ for bonded pairs of neighboring polymer beads on a chain.…”
Section: Model and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…We model the solvent as a Lennard-Jones (LJ) liquid and the polymer as linear chains of 100 beads connected by permanent bonds. All solvent and polymer beads have a mass m and interact through a standard LJ 12-6 pairwise potential, U LJ (r) = 4ǫ[(σ/r) 12 − (σ/r) 6 − (σ/r c ) 12 + (σ/r c ) 6 ], where r is the distance between the centers of two beads, ǫ the strength of interaction, and σ the size of beads. The cut off distance is r c = 3.0σ for all nonbonded pairs and r c = 2 1/6 σ for bonded pairs of neighboring polymer beads on a chain.…”
Section: Model and Methodologymentioning
confidence: 99%
“…These considerations have motivated many experimental studies on controlling the NP distribution and organization in a polymer brush so that certain functions can be realized. [4] The hybrid structure is determined collectively by the strength of enthalpic NP-polymer interaction, [7] the brush characteristics including grafting density, [8] thickness, [9] pattern, [10][11][12] composition, [13] and possible gradients of these properties, [14][15][16] and the solvent being used. [17] Various theoretical and computational techniques have been employed to study the interactions between NPs and a polymer brush, including the self-consistent field theory (SCFT), [18][19][20][21][22][23][24][25][26][27][28][29] Monte Carlo simulations, [30][31][32] molecular dynamics (MD) simulations, [33][34][35] dissipative particle dynamics (DPD), [36] and Brownian dynamics simulations.…”
Section: Introductionmentioning
confidence: 99%
“…30 In the optical tweezers experiments, NP location is controlled by a laser beam. Displacement of NP from the beam focus indicates the effective force due to NP-PB interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Displacement of NP from the beam focus indicates the effective force due to NP-PB interaction. Very recently, Steinbach et al 30 applied the optical tweezers to study interactions between charged NPs and a solid substrate functionalized with strong and weak polyelectrolyte chains. Depending on the pH, the authors observed NP binding to or repulsion from the brush and concluded that optical tweezers is a versatile method to directly probe NP-PB interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Processes occurring at solid-liquid interfaces are of critical importance for a variety of applications spanning diverse fields including geochemistry, environmental science, catalysis, solar energy, corrosion protection, and many others [1]. Examples of such processes include interactions involving (dis)charging of colloids [2][3][4][5][6][7][8], physisorption and chemisorption [9][10][11][12], (electro)chemical reactions, and photocharging [13], all of which involve evolution of the effective surface charge. In order to understand these processes, it is important to develop tools that enable systematic studies of these interactions, depending on the nature of the interface.…”
Section: Introductionmentioning
confidence: 99%